2006
DOI: 10.1111/j.1440-1843.2006.00903.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome in patients with lung cancer invisible on chest roentgenograms but detected only by helical computed tomography

Abstract: The aim of this study was to evaluate the prognosis for patients with lung cancer detected by helical CT but not by CXR. One hundred and thirty-seven asymptomatic patients with lung cancer diagnosed by annual mass screening of the chest were enrolled over a 7-year period. Five-year survival rates in patients with lung cancer detected only by helical CT (n = 19: CT-only detection group) and in patients with lung cancer visible by both CXR and helical CT (n = 118: control group) were evaluated, and clinical vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2006
2006
2008
2008

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Studies have reported an average tumor diameter of 33 mm among cancers detected during routine care, [33][34][35][36][37] 30 mm in patients undergoing CXR screening, 38 -40 and 16 mm in patients undergoing CT screening (all scans). 1,16,17,37,38,[41][42][43][44][45] For patients detected purely by an incidence scan during the course of CT screening the average size is approximately 13 mm. 1,42,44 Table 6 tabulates results of calculations based on reported average tumor sizes and doubling times according to the method of detection using the exponential growth model.…”
Section: Predictions On the Natural History From Doubling Timesmentioning
confidence: 99%
“…Studies have reported an average tumor diameter of 33 mm among cancers detected during routine care, [33][34][35][36][37] 30 mm in patients undergoing CXR screening, 38 -40 and 16 mm in patients undergoing CT screening (all scans). 1,16,17,37,38,[41][42][43][44][45] For patients detected purely by an incidence scan during the course of CT screening the average size is approximately 13 mm. 1,42,44 Table 6 tabulates results of calculations based on reported average tumor sizes and doubling times according to the method of detection using the exponential growth model.…”
Section: Predictions On the Natural History From Doubling Timesmentioning
confidence: 99%
“…The increase in advanced diagnosis techniques such as high resolution computed tomography (HRCT), which can detect small size or light density lung cancers [4], may be the main reason for the increase in limited resections [5]. Furthermore, some reports have shown that patients with lung cancer detected only by helical CT have a better prognosis than patients with lung cancer invisible on chest roentgenograms [6]. The situation appears to be gradually changing with respect to segmentectomy procedures.…”
mentioning
confidence: 99%
“…are under study. A study of 137 patients with lung cancer showed that those ( n = 19) with early disease detected only on CT, but not on CXR, had significantly better prognosis (5‐year survival 80% vs. 39%, respectively) than those with lung cancer visible on both CT and chest radiographs 9 . However, Shaipanich et al .…”
Section: Lung Cancermentioning
confidence: 99%
“…A study of 137 patients with lung cancer showed that those (n = 19) with early disease detected only on CT, but not on CXR, had significantly better prognosis (5-year survival 80% vs. 39%, respectively) than those with lung cancer visible on both CT and chest radiographs. 9 However, Shaipanich et al believed that no single modality will achieve sufficient accuracy as a sole screening tool, and combination with additional biomarkers may be more likely to succeed. 10 PET-CT is increasingly employed in the work-up of patients with lung cancer.…”
Section: Lung Cancermentioning
confidence: 99%